The mediating role of reporting tendencies of environmental news in the relationship between information sources and citizen’s environmental awareness via Southern Weekend - Ye, He; Mahamed, Mastura; Shari, Sharil Nizam (Redfame Publishing, 2023)
This article takes China's Southern Weekend Green newspaper as an example, selects 235 articles in Southern Weekend Green from 2018 to 2020. Conduct relevant research on environmental news reported in newspapers and magazines. Most of the previous studies focus on the classification of content, and there is no relevant research on the information source and the audience's environmental awareness. Therefore, the purpose of this study was to investigate the mediating role of reporting bias between information sources and the audience's environmental awareness. The research method adopts the quantitative research method, adopts the random sampling method to conduct a questionnaire survey on the respondents, and distributes a total of 392 questionnaires. Correlation analysis was carried out on the influence of different information sources on reporting tendency and dissemination effect, and SPSS was used for correlation test.